Pengaruh Pemberdayaan Peternak terhadap Aksesibilitas Sumber Daya Usaha Peternakan Sapi Potong Rakyat: Sebuah Refleksi Peraturan Pemerintah Nomor 6 Tahun 2013 - Sefi, Mohammad; Jadmiko, Mochammad Wildan; Harsita, Pradiptya Ayu; Amam, Amam (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Beef cattle are one of the national commodity strategies of the livestock subsector, so that no livestock business and livestock business development is inseparable from the support of various resources. The livestock farmer empowerment program in accordance with Government Regulation Number 6 of 2013 is expected to be able to increase livestock farmers' access to beef cattle farming business resources. The purpose of this study is to examine the effect of the empowerment program on the accessibility of beef cattle business resources, namely financial, technological, physical, economical, environmental, and social resources. The study was conducted in Purnama Village, Tegalampel Subdistrict, Bondowoso District, East Java Province. The study used qualitative and quantitative methods. Qualitative data collection used the Focus Group Discussion (FGD) and observation methods, while quantitative data collection used survey methods, namely by interview (oral survey) and filling out questionnaires (written survey). The study involved 122 beef cattle farmers (owning their own), which was determined by the requirement that respondents have at least 2 (two) cows (micro-scale). Data analysis used simple linear regression. The results of the study indicate that livestock farmers have a positive influence on livestock business resources, including financial, technological, physical, economical, environmental, and social resources. However, livestock farmers only significantly influence technological, environmental, and social resources, while other resources, such as financial, physical, and economical resources, have no significant influence. Livestock empowerment has a 22.09% impact on technological resources, a 23.80% impact on environmental resources, and a 30.30% impact on social resources.